Adoption of row planting technology and household welfare in southern Ethiopia, in case of wheat grower farmers in Duna district, Ethiopia - Tamirat, Negese; Abafita, Jemal (Asia-Pacific Journal of Science and Technology, 2021)
Adoption of yield enhancing row planting technologies is crucial for achieving agricultural growth and development. This study attempts to investigate the factors affecting adoption decision and its impact on income and expenditure in Duna district cross-sectional field survey data gathered in 2018-2019. However, technology adoption and farmers livelihood were poorly related due to lack comprehensive measure of agricultural productivity. A cross-sectional field survey was conducted among 375 wheat growers in Duna district, southern Ethiopia. Descriptive statistics and econometric methods such as binary logit regression and propensity score matching was employed for the data analysis. Sensitivity analysis developed to ensure the validity of the conditional independence assumption. The results of binary logit regression revealed that the technology participant was significantly affected by age, education status, size of family, off-farm income, land holding, livestock holding, quantity of fertilizer used, farmers training center, access to credit and extension services. Adoption was associated with a significantly higher crop yield and expenditure. Sensitivity analysis indicated that there is no hidden bias. The findings suggest that the role of technology adoption at farm level due to higher yield and income could translate in to reduced poverty. Extension office and another concern body should give an important attention to adoption decision which base for enhancing yield. The summary of this technique by policy makers and plan designers could bring better enhancement on wheat cultivator. Improving such a technique is crucial option to enhance wheat grower income, consumption expenditure and crop yield.